Congenital toxoplasmosis and prophylactic of the first level - Kwiecień, Katarzyna D.; Zielińska, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Taking under consideration the progress of modern medicine and natural sciences it seems that there are no diseases that we could not defeat or minimize by- symptoms but despite the great progress in the field of medicine there are still diseases and disorders hard to detect or treatment. The thesis is focused on the problem of congenital toxoplasmosis with by-symptoms of a very complicated kind. The evolution and development of T. gondii concerning fetus may cause not only it’s death but also other disorders of nervous system. They may occur even few years after the initial infection. This is the main reason for each population to lead a new diagnostic and preventive strategies which have very close connection with prophylactic of the first level and women’s educational needs, who are planning to become pregnant. The main aim of this article is to present the signs, symptoms, indicators and risk of Toxoplasma gondii but also the range of prophylactic treatment and educational needs.